Faktor Situasional dan Demografis sebagai Prediktor Niat Individu untuk Melakukan Whistleblowing - Hakim, Tito (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2017)
The purpose of this research is to examine and to provide empirical evidence about influence of seriousness of wrongdoing, status of wrongdoer and culture orientation on whistleblowing intentions. Respondents of this study are employees in one of Pratama tax office in Malang region. The sampling technique used is convenience sampling. It uses survey method to examine 67 employees in Pratama tax office with the help of Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that seriousness of wrongdoing and culture orientation (collectivism) positively influence whistleblowing intentions. This research also provide empirical evidence that status of wrongdoer doesn’t have significant effect on individual whistleblowing intentions